Carbohydrate Derived α,β-Unsaturated Enals (Perlin’s Aldehyde) as Chiral Synthon for the Synthesis of Privileged Scaffolds - Yadav, Yogesh; Tyagi, Rajdeep; Sagar, Ram (Current Organic Chemistry, 2025)
Perlin’s aldehyde is an α,β-unsaturated carbonyl compound with two well-defined chiral centres and a free hydroxy group. Since its discovery and synthesis by A. S. Perlin in 1975, it has been used as a flexible chiral synthon for synthesising natural products, their scaffolds and biologically significant compounds. Perlin’s aldehydes serve as useful starting materials in diversity-oriented synthesis (DOS) and chiral building blocks in organic synthesis. Currently, synthesising frameworks based on carbohydrates is at the forefront of organic synthesis. Inspired by the reactivity of Perlin’s aldehyde, various research groups worldwide used this molecule as a chiral synthon and published a number of research papers and a review article covering literature until 2012. This review covers recent advances in the synthesis of natural products, their scaffolds and other hetrocylic molecules, starting from perlin aldehyde, covering the literature from 2013 to till date.
Keywords: organic synthesis